Nieuwentijt’s defense of the Bible - Drozdek, Adam (Studia Warmińskie, 2021)
In his physico-theological book Nieuwentijt wanted 1. to prove the existence of God and His attributes from the makeup of nature; 2. to prove the veracity of the Bible by showing that many recent scientific discoveries can also be found in the Bible; 3. by showing who God was and by showing the reliability of the Bible in matters of natural knowledge, Nieuwentijt wanted to show that the spiritual message of the Bible related to personal salvation should also be trusted and thus atheists and unbelievers should give in to this message.